Evolutionary assembly of cooperating cell types in an animal chemical defense system. - Brückner, A.; Badroos, J.M.; Learsch, R.W.; Yousefelahiyeh, M.; Kitchen, S.A.; Parker, J. (Cell, 2021)
How the functions of multicellular organs emerge from the underlying evolution of cell types is poorly understood. We deconstructed evolution of an organ novelty: a rove beetle gland that secretes a defensive cocktail. We show how gland function arose via assembly of two cell types that manufacture distinct compounds. One cell type, comprising a chemical reservoir within the abdomen, produces alkane and ester compounds. We demonstrate that this cell type is a hybrid of cuticle cells and ancient pheromone and adipocyte-like cells, executing its function via a mosaic of enzymes from each parental cell type. The second cell type synthesizes benzoquinones using a chimera of conserved cellular energy and cuticle formation pathways. We show that evolution of each cell type was shaped by coevolution between the two cell types, yielding a potent secretion that confers adaptive value. Our findings illustrate how cooperation between cell types arises, generating new, organ-level behaviors.